(untitled) (Circe de clásicos y modernos, 2017)
Impressionism was a tendency that developed in the late nineteenth century European culture. Music was no stranger to that expression, with its appropriate ways for conveying the ethereal and evanescent. This article deals with the best known musicians of impressionistic tendencies: Claude Debussy, Erik Satie and Maurice Ravel, and their works on the classical antiquity: The Afternoon of a Faun by Debussy, Gimnopaedias, Gnossiennes and Socrate by Satie and Ravel’s Ballet on Daphnis and Chloé legend. It consists on a short review of their musical education, a description of the mentioned works, underlining those that were initially rejected and later became classics of piano and orchestral repertory.